Aspects of structures and depositional environment of sand bodies within tomboy field, offshore western Niger Delta, Nigeria (2009)
" Sand bodies deposited across normal growth faults and associated rollover anticlines are critical reservoirs for the accumulation of oil and gas. This paper addresses aspects of structures and depositional environments of some sand bodies within the Tomboy field, offshore western Niger Delta. Structural interpretation was undertaken to identify and assign faults found in the 3-D seismic volume. Time and depth structure maps in combination with well logs were used to produce for five horizons, namely: H1 to H5 and identify the depositional environments respectively. Two major growth faults (F4 and F7 which are normal, listric concave in nature), three antithetic (F1, F3 and F6) and two synthetic faults (F2 and F5) were identified. Structural closures identified as rollover anticlines, and displayed on the time/depth structure maps; suggest probable hydrocarbon accumulation at the downthrown side of the fault F4. Point bars, distributary channel and mouth bars, barrier island and tidal channels are the depositional environments. This study shows that the Tomboy field is made up of sand bodies deposited in different environments across normal, growth faults and associated rollover anticlinal structures. "